Evaluation of partial clinker replacement by sugar cane bagasse ash: CO2 emission reductions and potential for carbon credits - Fairbairn,E. M. R. (2012)
This work presents a study about the viability of possible CO2 emissions reductions scenarios for the cement manufacturing through the implementation of Clean Development Mechanisms (CDM) associated with the partial replacement of cement by sugar cane bagasse ash (SCBA). Studies on the thermal, chemical and mechanical behavior of concretes containing 5 to 20% of ash indicated that there is improvement on the performance of all analyzed properties and that the ash can be used as admixture on the cement manufacturing. The CO2 emissions of two hypothetical scenarios of CDM Project implementation in the state of São Paulo through this technology were evaluated based on the official and applicable methodology. The results show that there are emission reductions on both scenarios, even for the most unfavorable, evidencing the possibility of obtaining negotiable carbon credits.